Solutions by everydaycalculation.com
How to solve 43x + 7 = 5x + 3? Get the answer and stepwise instruction to solve linear equation in one one variable 𝒙.
We have 43x + 7 = 5x + 3
First, we move the x terms to the LHS and constant terms to the RHS of the equation, inverting the sign on the terms. This is also called transposing method.
Transposition is a faster method and combines the following two steps, were we to solve the equation by:
i) Subtracting 7 from both sides
ii) Subtracting 5x from both sides
Therefore, 43x - 5x = 3 - 7
or, 38x = -4
Next, divide both sides by 38, which is the coefficent of xNote: if a = b, then a ÷ c = b ÷ c
38x/38 = -4/38
x = -4/38
To simplify, divide both numerator and denominator by 2, which is the GCF of 4 and 38:
x = -2/19 or, x = -0.11